Frequency of Medically Unexplained Symptoms in Homeopathy References of - A Mahmoudian (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2012)
Background and Objectives: 25-50 percent of all patients who are visited by GPs, have complains that are not medically explained. Their management is a challenge for GPs. In homeopathy (a method of alternative medicine) these symptoms are important for selection of remedies and in an effort to treat them. This study aimed at describing this existing situation by investigating the frequency of such complaints in the patients under study. Methods: This study is a cross-sectional study conducted in Isfahan in 2008 on 240 Patients who were visited in some of the clinics affiliated to Isfahan university of medical sciences. The patients were selected by convenient method. Data were gathered by the questionnaire and analyzed via SPSS 13.5 software using Chi-Square test. Results: Out of 240 patients, 150 were women (%65.4) and 90 were men(34.6%). 75.4 percent were 20-40 years old. 1.7 percent had no symptoms, 31.3 had 1-5 symptoms and 40.8 percent had 6-10 symptoms. The females had more symptoms than males. Symptoms of mind, GI, sleep and miscellaneous ones were 81.3, 80.4, 72.1 and 87.1 percent, respectively. The most frequent symptoms in each group were intrusive thought, salivation in sleep, waking frequently and dyspnea wearing tight collared clothes. Only 10.97 percent of patient referred to the physicians for these symptoms. Conclusion: The symptoms registered in homeopathy references have notable prevalence in the society but most of people with such symptoms will not go to a doctor for examination and treatment Therefore, it is very important to carry out more research regarding these symptoms. General population should receive more information and physicians, in turn, should use appropriate methods of therapy for treating these patients.